Differential heparan sulfate dependency of the Drosophila glypicans. - Nakato, E.; Kamimura, K.; Knudsen, C.; Masutani, S.; Takemura, M.; Hayashi, Y.; Akiyama, T.; Nakato, H. (Journal of Biological Chemistry, 2024)
Heparan sulfate proteoglycans (HSPGs) are composed of a core protein and glycosaminoglycan (GAG) chains and serve as coreceptors for many growth factors and morphogens. To understand the molecular mechanisms by which HSPGs regulate morphogen gradient formation and signaling, it is important to determine the relative contributions of the carbohydrate and protein moieties to the proteoglycan function. To address this question, we generated ?GAG alleles for dally and dally-like protein (dlp), two Drosophila HSPGs of the glypican family, in which all GAG-attachment serine residues are substituted to alanine residues using CRISPR/Cas9 mutagenesis. In these alleles, the glypican core proteins are expressed from the endogenous loci with no GAG modification. Analyses of the dally[?GAG] allele defined Dally functions that do not require heparan sulfate (HS) chains and that need both core protein and HS chains. We found a new, dally[?GAG]-specific phenotype, the formation of a posterior ectopic vein, which we have never seen in the null mutants. Unlike dally[?GAG], dlp[?GAG] mutants do not show most of the dlp null mutant phenotypes, suggesting that HS chains are dispensable for these dlp functions. As an exception, HS is essentially required for Dlp's activity at the neuromuscular junction. Thus, Drosophila glypicans show strikingly different levels of HS dependency. The ?GAG mutant alleles of the glypicans serve as new molecular genetic toolsets highly useful to address important biological questions, such as molecular mechanisms of morphogen gradient formation.